Strategi Pengembangan Madrasah Tsanawiyah Swasta terhadap Kualitas Pendidikan Islam di Kecamatan Tellulimpoe Kabupaten Sinjai - Haerudin, Haerudin (Institut Agama Islam Negeri (IAIN) Bone, 2019)
The results showed that the strategy of the development of Mts in Kec. Tellulimpoe as a sub-national education where sisitem madrasa has a great role in feeding children Nations both in terms of his knowledge or knowledge for his religion, by entering the charge of education and education of social behavior based on Islamic values. Madrasah education issues in General can be seen from the two establishments, i.e. internal and external nature. Problems that are external such as the question of the political, economic, social, cultural, defense and security. In addition to the problem that is the external call, education also faced internal problems to management, such as institutional, educational personnel, curriculum, learning strategies, the quality of graduates and funds. Strategy for the development of formal education through establishing the madrasa-based management development and flagship madrasa. Quality Islamic education in Tellulimpoe can be seen from the construction and development of increased private Regency Sinjai madrasah in the planning of the construction of teacher competence, educational enhancement madrasa has been the planned construction of the competence of educators and educational so that run educational activities in madrasah in an efficient and effective manner. The strategy of development of Mts in improving the quality of Islamic education in district Tellulimpoe through increased competence of teachers has been planned through the work plan budget and plan of the madrasa serious madrasa. Every year discussed jointly by the head of the madrasa together stakeholders and form its activities namely conducting training, comparative study, seminars, workshops, and field of study as well as the MGMP do istighatsah.Hasil penelitian menunjukkan bahwa strategi pengembangan Mts di Kec. Tellulimpoe sebagai pendidikan daerah di mana sisitem madrasah memiliki peran besar dalam memberi makan anak-anak Bangsa baik dari segi pengetahuan atau pengetahuan untuk agamanya, dengan memasukkan biaya pendidikan dan pendidikan perilaku sosial berdasarkan nilai-nilai Islam. Persoalan pendidikan madrasah secara umum dapat dilihat dari dua pendirian, yaitu sifat internal dan eksternal. Masalah yang bersifat eksternal seperti masalah politik, ekonomi, sosial, budaya, pertahanan dan keamanan. Selain masalah panggilan eksternal, pendidikan juga menghadapi masalah internal manajemen, seperti kelembagaan, tenaga kependidikan, kurikulum, strategi pembelajaran, kualitas lulusan dan dana. Strategi untuk pengembangan pendidikan formal melalui pembentukan pengembangan manajemen berbasis madrasah dan madrasah unggulan. Pendidikan Islam yang berkualitas di Tellulimpoe dapat dilihat dari pembangunan dan pengembangan madrasah swasta Kabupaten Sinjai yang semakin meningkat dalam perencanaan pembangunan kompetensi guru, peningkatan mutu pendidikan madrasah telah menjadi rencana pembangunan kompetensi pendidik dan pendidikan sehingga menjalankan kegiatan pendidikan di madrasah dengan cara yang efisien dan efektif. Strategi pengembangan MTs dalam meningkatkan kualitas pendidikan Islam di kabupaten Tellulimpoe melalui peningkatan kompetensi guru telah direncanakan melalui anggaran rencana kerja dan rencana madrasah madrasah yang serius. Setiap tahun dibahas bersama oleh kepala madrasah bersama para pemangku kepentingan dan bentuk kegiatannya yaitu melakukan pelatihan, studi banding, seminar, lokakarya, dan bidang studi serta MGMP melakukan istighatsah.